Developing commute optimization system to minimize negative environmental impacts and time of business commuters. Issue 2 (1st January 2020) - Abdallah, Moatassem; Tawfik, Aly M.; Monghasemi, Shahryar; Clevenger, Caroline M.; Adame, Beranea A.
Abstract: The objective of this research is to develop a novel and innovative system, called Business + Commute Optimization System (B + COS) that is capable of identifying the optimal selection of individualized commute alternatives of employees in a business to minimize their greenhouse gas (GHG) emissions, air pollution, and commute time. B + COS is designed to identify the optimal travel behavior for each commuter ( e.g., drive car, carpool, use public transit, bike or walk) while maintaining convenience and incentivizing commuters using monetary incentives. The system consists of a geographical information system (GIS) and a multi-objective optimization model. The GIS is designed to measure and quantify business commute attributes such as emissions, commute cost, and time of each commute option. The multi-objective optimization model is designed to generate optimal trade-offs among two optimization objectives (1) minimizing equivalent social cost of GHG emissions and air pollution, and (2) minimizing total commute time of business commuters. Performance of the system is evaluated and verified using a case study of 21 commuters. Results show the capabilities of the new system in identifying Pareto-optimal solutions of the two optimization objectives for various tolerances of commute time increase ranging from 5 to 25 min. The promising results highlight the effectiveness of such an innovative system to minimize transportation-related emissions and commute time for businesses.